SAVI MODEL (SOMATIC, AUDITORIAL, VISUAL AND INTELLECTUAL) IN LEARNING CREATIVE DANCE FOR CLASS X STUDENTS OF SMA NEGERI 17 PANDEGLANG - Eneng diah; Alis Triena Permanasari; dwi junianti lestrari (Journal of Dance and Dance Education Studies, 2023)
Efforts to optimize the successful implementation of dance learning can be done by applying appropriate learning strategies and methods. The purpose of this study was to determine the process of learning creative dance through the SAVI model and the influencing factors. The research method used is descriptive qualitative, data collection techniques used are observation, interview and documentation techniques. The results of this study are in the form of a description of the creative dance learning process through the SAVI model, the activities implemented start from planning implementation and evaluation. In the planning stage, preparing an RPP (Learning Implementation Plan) adapted to the syllabus and preparing teaching materials. Then the implementation activities carried out in the learning process through the SAVI model consist of four stages, namely: introduction, delivery of material, creative dance practice and closing. Evaluation of the learning outcomes of creative dance using group dance practice tests with individual scores. The supporting factors are the enthusiasm for student learning and the teacher's role as a guide, while the inhibiting factors are the lack of a schedule for teaching dance.Kata Kunci: Proses Pembelajaran, Tari Kreasi, Banten Jawara